Silver Complexes of Substituted Triazione Thiones and Their Gravimetric Applications - Khadar, A.M.A.; Gajendragad, M.R. (Asian Journal of Chemistry, 2010)
Silver complexes of 4-amino-3-thio-1,2,4-triazin(4H)-5-one (ATT) and 4-amino-3-thio-6-phenyl-1,2,4-triazin(4H)-5-one (ATPT) are prepared and characterized by elemental analysis and infrared spectral data. The complexation being quantitative in ammoniacal tartrate medium and the complexes being thermally stable, non-hygroscopic and non-photosensitive in nature, their probable use as gravimetric reagents for the determination of miligram quantities of silver in complexes and alloys is proposed.